2009
DOI: 10.1007/s10551-009-0304-9
|View full text |Cite
|
Sign up to set email alerts
|

Confucius, Cars, and Big Government: Impact of Government Involvement in Business on Consumer Perceptions Under Confucianism

Abstract: China, Confucianism, government involvement, perceptions, preference, purchase intention,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Empirical research has shown that because of the ideology of "zhong", as manifested by the loyalty to superiors in a Confucian society, Chinese consumers tended to favor governmentrelated business enterprises over private firms or foreign ones that had not established connections with the Chinese government (7). In fact, 78% of the Chinese people considered their government credible, while only 38% of Americans con sidered their government credible, despite the higher rate of corruption in China (8).…”
Section: Zhong (Loyalty)mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research has shown that because of the ideology of "zhong", as manifested by the loyalty to superiors in a Confucian society, Chinese consumers tended to favor governmentrelated business enterprises over private firms or foreign ones that had not established connections with the Chinese government (7). In fact, 78% of the Chinese people considered their government credible, while only 38% of Americans con sidered their government credible, despite the higher rate of corruption in China (8).…”
Section: Zhong (Loyalty)mentioning
confidence: 99%
“…In the market, citizens' loyalty to the government is demon strated through their loyalty toward governmentrelated businesses. Consumers have a higher expectancy rate for governmentrelated businesses or products, compared with the private or nongovernmentrelated enterprises, which certainly benefits governmentrelated businesses (7).…”
Section: Zhong (Loyalty)mentioning
confidence: 99%
“…Confucianism, the backbone of Chinese philosophy (Chiu, 2003;Cho and Lee, 2001;Fan, 2000;Laurence et al, 1995;O'Keefe and O'Keefe, 1997;Wang and Juslin, 2009), plays a pivotal role in guiding Chinese thinking and behaviour (Fam et al, 2009;Lan et al, 2009;Nankervis and Ngok, 2007). Confucianism lays the foundation for Chinese social relationships (Warden and Chen, 2009) and business practices (Ackerman et al, 2009;Fam et al, 2009;Zhu, 2009). In China, the philosophical foundation for understanding how the world works is conceived less in terms of discrete objects than in terms of relationships; this Chinese correlative thinking results in an aesthetic appreciation of the quality of relationships which naturally entails an ethical dimension.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current context, Confucianism has gained significant favour. The focus of Confucianism on social relations seems to fit well in China's goals for social stability (Ackerman et al, 2009). A renewed interest in Confucian teachings also emerged, especially as these teachings were seen as a means of negating the entry of Western culture.…”
Section: Jssmentioning
confidence: 94%
“…It is a philosophical and religious system which is based on the teachings of the Chinese philosopher Confucius. Through the teachings of Confucius, the values of humaneness, righteousness, propriety, knowledge, integrity, loyalty, filial piety and continence have been described and applied (Ackerman et al, 2009;McDonald, 2012;Chunxia, 2010). In relation to education, Confucianism supports different virtues and values which are meant to highlight the importance of study in the lives of followers.…”
Section: Introductionmentioning
confidence: 99%